The Triterpenes of Kageneckia oblonga - Jorge Tapia-Merino; Lily Arrue; JosÃ© San MartÃn; Orlando MuÃ±oz (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
Three known triterpenes were isolated from leaf extracts of Kageneckia oblonga by conventional chromatographic methods: ursolic acid, benthamic acid and a third called Kc-III. The structure of Kc-III was determined by RMN spectroscopy, FT-IT and HR-MS. The compound was identified as fern-7-en-3Î²-ol (motiol), not previously reported in Kageneckia.